2000
DOI: 10.1128/jb.182.20.5749-5756.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RpoS (ς S )-Regulated Genes in Salmonella enterica Serovar Typhimurium

Abstract: The rpoS gene encodes the alternative sigma factor S (RpoS) and is required for survival of bacteria under starvation and stress conditions. It is also essential for Salmonella virulence in mice. Most work on the RpoS regulon has been in the closely related enterobacterial species Escherichia coli. To characterize the RpoS regulon in Salmonella, we isolated 38 unique RpoS-activated lacZ gene fusions from a bank of Salmonella enterica serovar Typhimurium mutants harboring random Tn5B21 mutations. Dependence on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
120
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(131 citation statements)
references
References 48 publications
11
120
0
Order By: Relevance
“…Moreover, MG1655 yncC and MG1655 have the same specific growth rate during the early exponential phase, but obtain different cell densities at the late exponential stage and stationary stage (the yncC mutant enters stationary stage with a significantly lower cell density, turbidity of 600 nm of 2.7 ± 0.2 vs 5.3 ± 0.1 for the wild-type strain). This suggests YncC functions at the late exponential stage and stationary stage, which are consistent with the finding that the homolog of E. coli yncC in the Gram-negative bacterium Salmonella enterica serovar typhimurium is under the regulation of the stationary-phase sigma factor s S (RpoS) (Ibanez-Ruiz et al, 2000). This mimics bacterial AI-2 internalization behavior (Xavier and Bassler, 2005) and also agrees with the concept that RpoS is intimately associated with E. coli quorum sensing (DeLisa et al, 2001a), which suggests that the quorum-sensing process, stress response process and biofilm development are tightly linked.…”
Section: Yncc Represses Ybimsupporting
confidence: 76%
“…Moreover, MG1655 yncC and MG1655 have the same specific growth rate during the early exponential phase, but obtain different cell densities at the late exponential stage and stationary stage (the yncC mutant enters stationary stage with a significantly lower cell density, turbidity of 600 nm of 2.7 ± 0.2 vs 5.3 ± 0.1 for the wild-type strain). This suggests YncC functions at the late exponential stage and stationary stage, which are consistent with the finding that the homolog of E. coli yncC in the Gram-negative bacterium Salmonella enterica serovar typhimurium is under the regulation of the stationary-phase sigma factor s S (RpoS) (Ibanez-Ruiz et al, 2000). This mimics bacterial AI-2 internalization behavior (Xavier and Bassler, 2005) and also agrees with the concept that RpoS is intimately associated with E. coli quorum sensing (DeLisa et al, 2001a), which suggests that the quorum-sensing process, stress response process and biofilm development are tightly linked.…”
Section: Yncc Represses Ybimsupporting
confidence: 76%
“…Various studies have shown rpoS null mutants to display increased susceptibility to acid pH and attenuated virulence in BALB/c mice after the peroral route of infection (Fang et al, 1992;Lee et al, 1995;Coynault et al, 1996;Bearson et al, 2006;Domínguez-Bernal et al, 2008;Karasova et al, 2009). Although many genes with known functions in stress responses have been identified within the rpoS regulon of S. Typhimurium (Ibanez-Ruiz et al, 2000), further work is required in order to determine the nature of the full regulon and to elucidate the environmental factors that influence its expression within specific microenvironments in the host.…”
Section: Synthesis Of Acid Shock Proteins (Asps)mentioning
confidence: 99%
“…At least 70 genes are known to be regulated by RpoS, with many more probably still to be found (6,11). Moreover, the functions of RpoS and the known RpoS-regulated genes are not completely understood (11).…”
Section: C)mentioning
confidence: 99%
“…At least 70 genes are known to be regulated by RpoS, with many more probably still to be found (6,11). Moreover, the functions of RpoS and the known RpoS-regulated genes are not completely understood (11). Though the rpoS-deleted strain of S. enterica serovar Typhi exhibited low cytotoxicity in our previous work (12), the safety of rpoS-deleted virulencedefective strains GTC 3P460 and GTC 3P461 was checked in this work to ensure their suitability for use in a teaching laboratory.…”
Section: C)mentioning
confidence: 99%
See 1 more Smart Citation